2022
DOI: 10.3390/ijms231911990
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Therapy in Metastatic Melanoma: Focus on MAPK Pathway Inhibition

Abstract: Gut microbiome (GM) and its either pro-tumorigenic or anti-tumorigenic role is intriguing and constitutes an evolving landscape in translational oncology. It has been suggested that these microorganisms may be involved in carcinogenesis, cancer treatment response and resistance, as well as predisposition to adverse effects. In melanoma patients, one of the most immunogenic cancers, immune checkpoint inhibitors (ICI) and MAPK-targeted therapy—BRAF/MEK inhibitors—have revolutionized prognosis, and the study of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…For fiber intake, the cut-off value of 25 g/day was chosen because it is the amount recommended by the Dietary Reference Values for Italian (LARN) [57] and European (EFSA) [58] populations. Furthermore, adherence to the Mediterranean diet was determined using the Italian Mediterranean Index (IMI) [59], which defined the following 4 categories: minimal adherence (0-1), discreet adherence (2-3), good adherence (4-5), and maximal adherence (6)(7)(8)(9)(10)(11).…”
Section: Physical Activity and Dietary Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…For fiber intake, the cut-off value of 25 g/day was chosen because it is the amount recommended by the Dietary Reference Values for Italian (LARN) [57] and European (EFSA) [58] populations. Furthermore, adherence to the Mediterranean diet was determined using the Italian Mediterranean Index (IMI) [59], which defined the following 4 categories: minimal adherence (0-1), discreet adherence (2-3), good adherence (4-5), and maximal adherence (6)(7)(8)(9)(10)(11).…”
Section: Physical Activity and Dietary Questionnairesmentioning
confidence: 99%
“…Indeed, both experimental and human studies have demonstrated the importance of GM in modulating the efficacy of anticancer therapy and patients' susceptibility to side effects [4]. With particular reference to melanoma, GM is known to play a leading role in the therapeutic response, especially to immune checkpoint inhibitors, by promoting local and systemic inflammation or inducing immunosuppressive phenotypes, thereby enhancing or counteracting the anti-tumor immune response [5][6][7][8][9]. This awareness has paved the way for several clinical trials aimed at manipulating GM (e.g., through diet, bacterial consortia, or even fecal microbiota transplantation) toward a more favorable profile associated with better prognosis and overall survival [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%